The influence of the historical development of the state on the formation of its national power - Tkach , Mykola; Ablazov , Ivan; Komarnytsʹkyy Ihor (Social Development and Security, 2020)
The article is of interest to specialists, both in the economic and defense spheres, who are engaged in research on the issues of meeting the military and economic needs of states, both in peacetime and in wartime. The aim of the article is to study the dependencies in the development of the economic potential of the state and the increase of its military power, on the example of the historical development of Great Britain. The scientific task was solved by identifying trends in socio-economic and political development of Great Britain. In the process of achieving the goal of the study the following methods of scientific knowledge were used: historical analogy, analysis, synthesis, induction, deduction, system approach. The analysis of the sources shows that the issue of developing the military and economic potential of the states is given a lot of attention, especially the interest in this issue began to grow with the beginning of the war in Syria and Ukraine. The vast majority of countries in the world are gradually increasing their defense budgets, thus increasing global military power and tension. The issue of military power is increasingly receiving the attention of the top political leadership of the advanced states of the world, which cannot but arouse the interest of scientists. Research on historical analogies, identical to past events, can help identify patterns and predict scenarios for future events, which will help states better prepare for potential threats. The article analyzes the development of socio-economic and political system of Great Britain over hundreds of years, reveals certain trends and patterns of their impact on the military and economic potential of the state.